Ecological science and tomorrow's world - May, R (Royal Society Publishing, 2010)
Beginning with an outline of uncertainties about the number of species on Earth today, this paper addresses likely causes and consequences of the manifest acceleration in extinction rates over the past few centuries. The ultimate causes are habitat destruction, alien introductions, overexploitation and climate change. Increases in human numbers and per capita impacts underlie all of these. Against a background review of these factors, I conclude with a discussion of the policy implications for equitably proportionate actions - and of the difficulties in achieving them.